+0  
 
0
173
1
avatar+4269 

Help 1

NotSoSmart  Mar 8, 2018
 #1
avatar+92367 
+1

1.  We probably only need two terms, NSS

First term  = 12 (1)  - 11  = 1

Second term  = 12(2)  - 11  =  13

It appears that the third answer is good

 

2. The "formula"  is

 

a = an-1  + 13

The next term  is

57 + 13  =

70

Second answer

 

3.  A litle tricky, NSS......it appears that the nth term is

 

10  - .5 ( n - 1)

 

We need the 8th term....so we have.....

 

10 - .5 ( 8 - 1)  =

10 - .5 (7)  =

10  - 3.5 =

6.5   ⇒    first answer

 

 

 

cool cool cool

CPhill  Mar 8, 2018

15 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.